Extractive Spectrophotometric Determination of Cyclopentolate Hydrochloric - Reddy, M.N.; Kanna Rao, K.V.; Murthy, T.K.; Reddy, M.D. (Asian Journal of Chemistry, 2010)
Two simple and sensitive extractive spectrophotometric methods have been developed for the determination of cyclopentolate hydrochloride in bulk samples and in pharmaceutical preparations which are based on the formation of coloured complexes of the drug with reagents such as bromothymol blue and methyl orange. The ion pair complexes formed were quantitatively extracted into .chloroform under the experimental conditions. All the variables have been optimized and the concentration measurements are reproducible within a relative standard derivation of 1.0% and recoveries are 99-101 %.